Social Origins of Modern Terrorism, 1860–1945. (1st January 2023) - Tschantret, Joshua
Abstract: Why did modern terrorism arise as a form of political violence? Scholars have located its origins in the mid-nineteenth century, a development that culminated in a global wave of terrorism and contributed to the outbreak of World War I. Despite consensus on its period of origin, we lack any explanation for why this development occurred. This article forwards a social theory for the origins of modern terrorism. Civic associations, which proliferated globally in the nineteenth century, provided the opportunity and motivation for the development of terrorism. Associations not only fostered the social and human capital necessary for terrorism; they also frequently generated grievances through an inability to enact political change and via ideological propaganda. I test this theory using an original global dataset of terrorist groups formed between 1860 and 1945. Statistical analysis reveals that cities with a YMCA, an exogenous indicator of associationism, were much more likely than those without to see the formation of terrorist groups. Additionally, terrorist groups are formed during civil wars, indicating that armed conflict can spur dramatic innovations in violent contention.